2013
DOI: 10.1002/stc.1604
|View full text |Cite
|
Sign up to set email alerts
|

Spectral damage index for estimation of breathing crack depth in an aluminum plate using nonlinear Lamb wave

Abstract: SUMMARY In the present study, generation of higher harmonics as a result of nonlinear interaction of Lamb wave with a transverse breathing crack in a thin aluminum plate is explored through experiments and finite element simulation. Piezoelectric wafer transducers are used for generating and sensing of Lamb wave in the experiments. In the finite element simulation, a breathing crack is modeled using contact elements. Augmented Lagrangian algorithm is used for solving the contact problem. The crack faces open a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…In the case of a linear material, frequency of the received wave signal is the same as that of the excited wave, whereas higher harmonics are observed in the received wave signal for a nonlinear material . The material nonlinearity is either inherent or damage induced.…”
Section: Materials Nonlinearity Estimation Using Lamb Wavesmentioning
confidence: 98%
“…In the case of a linear material, frequency of the received wave signal is the same as that of the excited wave, whereas higher harmonics are observed in the received wave signal for a nonlinear material . The material nonlinearity is either inherent or damage induced.…”
Section: Materials Nonlinearity Estimation Using Lamb Wavesmentioning
confidence: 98%
“…The size of the elements must be sufficiently small for there to be at least 10 nodes per wavelength of the propagating wave. 15,16 Only A 0 and S 0 modes of Lamb wave are involved in the analysis and A0 mode has the smaller wavelength at 204 kHz which is 6.545 mm. Accordingly, the element size of 0.5 mm is used for the simulation.…”
Section: Finite Element Simulationmentioning
confidence: 99%
“…The accuracy in the integrations can be stated in terms of period elongation and amplitude decay. 15,16 In the FE simulation of Lamb wave propagation, both period elongation and amplitude decay affect the group velocity. Therefore, a convergence study is carried out as shown in Tables 1 and 2.…”
Section: Finite Element Simulationmentioning
confidence: 99%
“…The information about these features of the material can be obtained using ultrasonic waves. The ultrasonic waves propagating through such material produce additional wave components with frequencies multiple of the excitation frequency called as higher harmonics . The higher harmonics generation takes place in waves because of the material nonlinearity, classified as the classical nonlinearity .…”
Section: Introductionmentioning
confidence: 99%